Academic Language in Diverse Classrooms : English Language Arts, Grades 3-5:Promoting Content and Language Learning. - Gottlieb, Margo (SAGE Publications, 2013)
Make every student fluent in the language of learning. The Common Core and ELD standards provide pathways to academic success through academic language. Using an integrated Curricular Framework, districts, schools and professional learning communities can: Design and implement thematic units for learning Draw from content and language standards to set targets for all students Examine standards-centered materials for academic language Collaborate in planning instruction and assessment within and across lessons Consider linguistic and cultural resources of the students.